Optimization solvent sublation of dyes - Obushenko, Tetiana; Sanginova, Olga; Tolstopalova, Nataliia; Bondarenko, Serhii; Zahurska, Daria (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of treatment of wastewater contaminated with dyes by solvent sublation. Synthetic dyes are toxic, carcinogenic, and mutagenic, they cause serious problems with human health and are not subject to biological decomposition. Thus, there is an urgent need to devise cost-effective and environmentally safe approaches to the treatment of wastewater containing dyes before their discharge into the environment. A solvent sublation technology is proposed, which combines the advantages of ionic flotation and liquid extraction. The influence of process parameters on the efficiency of solvent sublation treatment of wastewater containing synthetic dyes has been investigated to ensure maximum efficiency (minimum values of residual pollutant concentrations). The dependences of purification efficiency for four dyes on the selected parameters such as pH, initial pollutant concentration, gas consumption and surfactant:dye ratio have been experimentally obtained. Based on the research, a mathematical apparatus of the STAR system was used to construct a 2nd-order mathematical regression model. The approximation error is 0.834; therefore, the proposed model describes the experimental data with a reasonable degree of accuracy. The stated optimization problem was solved by using the "OPTIMIZ-M" program; the optimal process conditions were determined, under which the maximum removal of dyes (97.20 %) is achieved: – pH: 6; – initial pollutant concentration: 20 mg/dm3; – surfactant:dye ratio: 1.5:1; – gas flow rate: 140 cm3/min. Optimizing solvent sublation treatment provides high quality wastewater treatment at minimal costs, reducing dye emissions into the environment, which could potentially increase the competitiveness of enterprises in the market